AI use in academic research: Examining the mediating effect of user experience and the moderating effect of disciplinary context on perceived integrity - Abubakar, Said; Adan, Mohamed Yusuf (Frontiers in Education, 2026)
The study investigates academic researchers’ use of AI in higher education research, drawing on the Unified Theory of Acceptance and Use of Technology (UTAUT) and integrity-trust frameworks. It examines the mediating effect of user experience and the moderating effect of disciplinary context on perceived integrity. A quantitative cross-sectional design was employed, collecting data via questionnaire from a sample of 100 academic researchers and lecturers across universities in Mogadishu, Somalia. Data analysis using SPSS and JAMOVI (PROCESS macro) involved correlation, mediation (bootstrapping), and moderation analyses. The overall trend in the findings suggests a positive, and growing, acceptance of AI for academic research as researchers believe it helps them produce better research outcomes. User experience mediates significantly the relationship between AI use and perceived integrity but disciplinary context does not moderate this relationship. Though perceived integrity is generally high, the researchers have some concerns about the reliability and ethical use of AI in research.